Growth and unemployment in the presence of trend inflation - Mewael Tesfaselassie (Kiel Institute for the World Economy (IfW), 2014)
The standard search model of unemployment predicts, under plausible assumptions about household preferences, that disembodied technological progress leads to higher unemployment. This prediction is at odds with the experience of industrialized countries in the 1970s. This paper shows that augmenting the model with nominal price rigidity goes towards reconciling the model's prediction. In the presence of nominal price rigidity faster growth is shown to lead to lower unemployment if the rate of inflation is relatively high, as was the case in the 1970s. In general, the effect of growth on unemployment is shown to be non-monotonic. There is a threshold level of inflation below (above) which faster growth leads to higher (lower) unemployment.
Keywords: E24; E31; 330; growth; trend inflation; unemployment